Rancang Bangun Sistem Layanan Bebas Laboratorium Menggunakan Pengaya (Add-Ons) Autocrat - S Sriyadi; David Mubarok; Ria Ika Maharani; Endah Peniati (UPT Laboratorium Terpadu, Universitas Diponegoro, 2022)
Laboratory-Free Services at the Biology Laboratory of Semarang State University are currently carried out online, but there are several shortcomings, including verification of data and document entries, as well as the creation of a laboratory-free certificate is still processed manually. The process of printing a laboratory-free certificate makes services inevitable from the use of paper. in addition, manual processes allow for data errors as well as taking longer. The purpose of this study was to design a laboratory-free service system using Autocrat Add-ons. The methods used in this study include interviews, observations, system design and testing of laboratory-free service systems using the blackbox method. The results of this study are in the form of a system that utilizes Autocrat Add-ons in laboratory-free services. All service processes can be done at any time online, as long as they are connected to the internet. Autocrat add-ons convert data entry into laboratory-free certificates. The results are sent directly to the student's email address so as to make it more paperless. From the results of the black box test, it shows that the laboratory free service system can run well as expected including aspects of short links, google forms, and autocrat add-ons functions. Theconclusion of this study is that the free service of the FMIPA UNNES biological laboratory was carried out online using the Autocrat add-ons (Add-ons) to be more effective, efficient and paperless